2020
DOI: 10.24086/cuejhss.v4n1y2020.pp41-45
|View full text |Cite
|
Sign up to set email alerts
|

Consumers Loyalty Indicator as a Drivers for Satisfaction

Abstract: This study focuses on understanding the leading indicators of loyalty among food and nourishments shoppers in two Syrian Malls, Cham City Centre and Massa Plaza, both located in Damascus, the capital of Syria. The research uses descriptive approach; the data were collected from a questionnaire distributed to 110 shoppers in the two shopping malls, 100 valid responses divided (50 answers from Cham City Centre, and 50 from Massa Plaza Mall). The data were analyzed using Statistical Package for Social Science to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
1
16
0
1
Order By: Relevance
“…However, KS can be described as a social interaction culture incorporating the interchange of knowledge, feelings, and abilities among individuals throughout the department or organization (Abd-Mutalib et al, 2017;. Meanwhile, KS aims to share expertise from fundamental understanding to specialist understanding in specific field (Massoudi, 2020;Wu and Zhu, 2012). KS considers essential because it can show the organization an excellent public reputation.…”
Section: A Ksmentioning
confidence: 99%
See 1 more Smart Citation
“…However, KS can be described as a social interaction culture incorporating the interchange of knowledge, feelings, and abilities among individuals throughout the department or organization (Abd-Mutalib et al, 2017;. Meanwhile, KS aims to share expertise from fundamental understanding to specialist understanding in specific field (Massoudi, 2020;Wu and Zhu, 2012). KS considers essential because it can show the organization an excellent public reputation.…”
Section: A Ksmentioning
confidence: 99%
“…In developing countries, most of the prior studies conducted in Malaysia (Cheng et al, 2009;Fauzi et al, 2018;Fauzi et al, 2019;Rahman et al, 2015). Meanwhile, limited studies were conducted in Middle East countries (Al-Delawi and Ramo, 2020;Al Delawi, 2019;Alhawary and Assistance, 2017;Mahmood et al, 2019;Massoudi, 2020), particularly among academic staff in the Iraqi setting (Massoudi and Hamdi, 2019;Mousa et al, 2019). The purpose of this study is to examine the impact of ATT, SN, and PBC on KS among academic staff at private universities in Erbil.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Dick & Basu., (1994) stated that loyalty is also known as the purchase by the customer from the same store (a specific store) permanently or by all or most of his needs from this store, because of the www.ijsser.com positive trend that of the customer towards this store. This is supported also by Massoudi (2020) he stated that loyalty is the consistent identification of consumers with their favorite store. Hanzaee & Farsani., (2011) indicated that high-level customer loyalty means high market share and the ability to request relatively high prices compared to others' prices; loyal consumers are more likely to buy back the same service or brand, and provide a positive spoken word and are willing to pay a premium price.…”
Section: The Concept Of Loyaltymentioning
confidence: 70%
“…Finally, the studies by (Dwivedi & Merrilees., 2016;Thaichon & Jebarajakirthy 2016;Ali et al 2016) have measured the intentions customer's loyalty and gauged the attitudinal and behavioral loyalty. Lastly, it is vital for businesses to recognize the connection between shopper satisfaction and loyalty (Massoudi, 2020). Satisfaction of the customer is a vibrant feature in increasing customer loyalty.…”
Section: The Concept Of Loyaltymentioning
confidence: 99%
“…There are many factors that can affect consumer behavior, including internal factors such as perception, education, motivations and personal considerations, and external factors such as culture, society, and customs. Another important factor that may be recognized by uncertainty and instability is the influences of product marketing (Thabit and Raewf, 2018), (Panwar et al, 2019), (Massoudi, 2020).…”
Section: The Influences Of Product Marketing On Consumer Behaviormentioning
confidence: 99%